Ultra-estrutura e citoquímica dos túbulos de malpighi de larvas de diatraea saccharalis (Lepidoptera: Crambidae) não parasitadas e parasitadas por cotesia flavipes (Hymenoptera : Braconidae) - Rigoni, Gislei Maria (2014)
The main pest that parasitizes sugarcane is Diatraea saccharalis (Fabricius, 1794) (Lepidoptera: Cambridae), which in its larval stage penetrates the sugarcane cane, the insult caused by the pest is related to the opening of galleries on the high Of the plant that allows the entrance of fungi, breakage by the decrease of the resistance against the wind, aerial rooting, death of the apical buds, among others. Also in the process of industrialization there are considerable losses as the production of inverted sugar and problems in the fermentation. The attack of the sugarcane borer on 1% of the stalks can reduce the sugar production by 35 kg. And in 30 liters of alcohol per hectare. In Brazil, the area estimated for the years 2012/2013 is 8.5 million hectares, due to the importance of this crop, the control of this pest has been researched for a long time, among them the use of natural enemies such as the Cotesia flavipes CAMERON, 1891) (Hymenoptera: Braconidae), which proved to be one of the most efficient resources in the control of sugarcane borer. C. flavipes is a wasp native to Asia, introduced in Brazil in 1971 as an endoparasite of Diatraea saccharalis. The female deposited its eggs, approximately 60, introducing its ovopositor apparatus in the body of the D. saccharalis caterpillar after the hatching of the egg the larva of the wasp develops in the hemolymph of the caterpillar, in approximately 15 days occurs the crushing of C. flavipes forming masses And breaking the epidermis of the caterpillar, thus promoting his death. Because it is a cenobionte parasite, it preserves the life of the host until its cycle is completed, although the cenobionite parasites produce changes in the hemolymph, endocrine system and immune system changes in the hosts, which is of paramount importance for the life cycle of the host. Parasitoid The object of study of this work are the tubules of Malpighi (TM), the main organs of excretion of insects, and the action of C. flavipes parasitism on this structure. In D. saccharalis larvae the TMs are adhered along the digestive tract, from the median region of the mesentero to the end of the posterior intestine where they form the cryptofridial arrangement, just below Of the sphincter of the pyloric region one can perceive the exact insertion site of the tubules in the intestine, this insertion is characterized by the presence of a saculiform structure called ampulla. In most insects the TMs are formed by two types of cells, the main or secretory cells and the resorptive cells. As a result of this research, two proposals were developed. In the first one, the analyzes of the TM ultramorphology of non - parasitized D. saccharalis larvae and five and nine days of parasitism by C. flavipes were carried out by means of scanning electron microscopy and electron microscopy of Transmission, an increase of hemocytes and the presence of teratocytes in the parasitized larvae can be observed, the presence of hemocytes indicates the immune response of D. saccharalis and the teratocytes are cells derived from the embryonic tissue of C. flavipes that aid in the development of Parasitoid. Two types of TM-forming cells, secretory cells, with well-developed cytoplasm, apical microvilli in contact with the lumen, base invaginations in the form of labyrinths, electron-dense vesicles, profuse mitochondria, including microvilli and resorptive cells, With less amount of microvilli and mitochondria, undeveloped cytoplasm which determines a greater caliber of luminal formation. On the ninth day of parasitism, vacuolated mitochondria and myelinic bodies were observed. The second proposal consisted of the determination of the presence of proteins, neutral carbohydrates, lipids and calcium salts, as well as the determination of the TM patterns of unparasitized and parasitized larvae by means of cytochemical tests. The analyzed regions of the TM responded positively to the presence of the molecules studied, there were no significant differences between unparasitized and parasitized larvae, the regions of the cells that reacted most intensively to the dyes were the basal regions and microvilli, the calcium salts were found in higher concentrations In the region of the rectum of the tubules. The esterases showed differences between the TM of larvae not parasitized and parasitized by C. flavipes.